Clarification of the identity of deep-sea crab Tymolus uncifer (Ortmann, 1892) and validation of Tymolus melanommus (Doflein, 1904) (Decapoda: Brachyura: Cyclodorippidae) - Komai, Tomoyuki (Zootaxa, 2023)
Examination of material from Japanese waters has disclosed that two species have been confounded under Tymolus uncifer (Ortmann, 1892) (Decapoda: Brachyura: Cyclodorippidae) in previous literature. The identity of Tymolus uncifer sensu stricto is clarified in reference to the lectotype, and the second taxon is herein attributed to T. melanommus (Doflein, 1904), which was originally recognised as a “forma” of T. uncifer with one specimen from off Kenya and one specimen from Japan. A lectotype is herein selected for T. melanommus in the interest of nomenclatural stability. Differentiating characters between the two species are assessed in detail, and those two species are compared also with T. glaucommus (Alcock, 1894), T. similis (Grant, 1905), T. brucei Tavares, 1991, T. daviei Tavares, 1997, T. hirtipes Tan & Huang, 2000 and T. globosus Spiridonov & Türkay, 2007, all of them are considered as valid. Sexual dimorphism and ontogenetic variation are seen in the relative length and stoutness of the pereopods 2 and 3 in T. uncifer and T. melanommus, but the morphometric characters derived from the two pereopods are useful as diagnostic at comparison between same sex in adults. Comparison of partial fragments of the mitochondrial COI and 16S rRNA gene sequences strongly supports that the two taxa are distinct. Previous records of T. uncifer, including fossil records, are reviewed based on the present findings. Tymolus uncifer and T. melanommus are restricted to Japanese waters at present.